Digital micromirror device projection printing system for meniscus tissue engineering - Grogan, Shawn P.; Chung, Peter H.; Soman, Pranav; Chen, Peter; Lotz, Martin K.; Chen, Shaochen; D’Lima, Darryl D. (Acta biomaterialia, 2013)
Meniscus degeneration due to age or injury can lead to osteoarthritis. Although promising, current cell-based approaches show limited success. Here we present three-dimensional methacrylated gelatin (GelMA) scaffolds patterned via projection stereolithography to emulate the circumferential alignment of cells in native meniscus tissue. Cultured human avascular zone meniscus cells from normal meniscus were seeded on the scaffolds. Cell viability was monitored, and new tissue formation was assessed by gene expression analysis and histology after 2weeks in serum-free culture with transforming growth factor β1 (10ngml−1). Light, confocal and scanning electron microscopy were used to observe cell–GelMA interactions. Tensile mechanical testing was performed on unseeded, fresh scaffolds and 2-week-old cell-seeded and unseeded scaffolds. 2-week-old cell–GelMA constructs were implanted into surgically created meniscus defects in an explant organ culture model. No cytotoxic effects were observed 3weeks after implantation, and cells grew and aligned to the patterned GelMA strands. Gene expression profiles and histology indicated promotion of a fibrocartilage-like meniscus phenotype, and scaffold integration with repair tissue was observed in the explant model. We show that micropatterned GelMA scaffolds are non-toxic, produce organized cellular alignment, and promote meniscus-like tissue formation. Prefabrication of GelMA scaffolds with architectures mimicking the meniscus collagen bundle organization shows promise for meniscal repair. Furthermore, the technique presented may be scaled up to repair larger defects.